Investigating genotoxicity of Eleusine indica by micronuclei assay in albino rats - Hannah Edim, Etta; Ekei Victor, Ikpeme; Effiom, Helen Offiong (African Journal of Biological Sciences, 2019)
Genotoxicity of Eleusine indica (Nkim enang: Efik) was investigated in the Wister strain albino rat (Rattus novergicus). Nine (9) male and nine (9) female rats were randomly assigned to three (3) groups, of which two were exposed to the aqueous extract of E.indica – Group A (control-no extract)), Group B (50 mg/kg BW of E. indica) and Group C (100 mg/kg BW of E. indica). This was administered to the rats by oral gavage for 14 days after which the peripheral blood from the tail tips were collected and assayed for the presence of micronuclei, following standard procedures. Proximate analysis and phytochemical screening of the herb extract was carried out. Results obtained showed that E. indica did not cause any significant (P > 0.05) increase in the incidence of micronucleated polychromatic erythrocytes in rat peripheral blood at any of the doses administered. The polychromatic: normochromatic erythrocyte (PCE: NCE) ratio was found to be in the range of 0.50 ± 0.11 to 0.55 ± 0.02. Also, the aqueous herb extract is rich in Carbohydrates (76.17%) and Tannins (21.76%). Mean body weights (MBW) of rats showed normal distribution throughout the duration of the investigation. The results of this study demonstrate that E. indica does not confer any genotoxicity in mammals. Further in-depth study on its efficacy is recommended.
Keywords: Bull grass, Medicinal plants, Toxicology, Nucleated cells, Negative genotoxicity